2006
DOI: 10.4049/jimmunol.177.10.6991
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of CXCL10 Is Necessary for Endothelial Cell Presentation and In Vivo Activity

Abstract: The chemokine IFN-γ-inducible protein of 10 kDa (IP-10; CXCL10) plays an important role in the recruitment of activated T lymphocytes into sites of inflammation by interacting with the G protein-coupled receptor CXCR3. IP-10, like other chemokines, forms oligomers, the role of which has not yet been explored. In this study, we used a monomeric IP-10 mutant to elucidate the functional significance of oligomerization. Although monomeric IP-10 had reduced binding affinity for CXCR3 and heparin, it was able to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 42 publications
0
80
1
Order By: Relevance
“…It has been shown that immobilized chemokines (including IP-10 and RANTES) presented by endothelial cells are critical for haptotaxis (55,56). More recently, oligomeric but not monomeric CXCL10 presented by endothelial cells via GAG was found to be essential for effector T cell recruitment (57). In this study, retention of alloreactive CD8 T cells in the peripheral blood might represent less efficient arresting of alloreactive CD8 T cells on site of extravasation without Cxcr3.…”
Section: Figure 7 Cxcr3mentioning
confidence: 81%
“…It has been shown that immobilized chemokines (including IP-10 and RANTES) presented by endothelial cells are critical for haptotaxis (55,56). More recently, oligomeric but not monomeric CXCL10 presented by endothelial cells via GAG was found to be essential for effector T cell recruitment (57). In this study, retention of alloreactive CD8 T cells in the peripheral blood might represent less efficient arresting of alloreactive CD8 T cells on site of extravasation without Cxcr3.…”
Section: Figure 7 Cxcr3mentioning
confidence: 81%
“…This unusual structural characteristic of CXCL10 provides an explanation for the ability of CXCL10 to bind to both CXCR3 and CCR3 receptors (33). Another stereotypical oligomerization of CXCL10 provides an additional source of structural diversity (3) which is essential for CXCL10 to recruit activated T cells that bind to endothelial cells and subsequently trans-migrate in vivo (34). This hypothesis was supported by Campanella et al (34), who determined that CXCL10 knockout mice lose their ability to recruit activated CD8+ T cells into their airways due to the presence of the N-methyl group disrupting the interaction of hydrogen bonds between the main chains, preventing the formation of dimers and oligomerization.…”
Section: Cxcl10 Gene Structure Function and Signaling Pathwaysmentioning
confidence: 99%
“…Another stereotypical oligomerization of CXCL10 provides an additional source of structural diversity (3) which is essential for CXCL10 to recruit activated T cells that bind to endothelial cells and subsequently trans-migrate in vivo (34). This hypothesis was supported by Campanella et al (34), who determined that CXCL10 knockout mice lose their ability to recruit activated CD8+ T cells into their airways due to the presence of the N-methyl group disrupting the interaction of hydrogen bonds between the main chains, preventing the formation of dimers and oligomerization. In vitro, the N-methylated Leu27 monomeric mutants were capable of inducing CXCR3 internalization and the chemotaxis of CD8+ T cells expressing CXCR3, but this induction required at least ten times higher concentrations than wild-type CXCL10; heparin and CXCR3 binding were noted, but at greatly reduced efficacy.…”
Section: Cxcl10 Gene Structure Function and Signaling Pathwaysmentioning
confidence: 99%
“…163 They help to establish a chemotactic gradient, protect chemokines from proteolytic cleavage, and have a role in oligomerization. [164][165][166][167] It has been postulated that interfering with GAG-chemokine interactions could be a potential therapeutic target, however, inherent complexities of this system has prevented significant progress. 25 While not affecting their ability to bind to their receptor(s), the truncation of the N terminus eliminates the signaling potential of many chemokines.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%